2001
DOI: 10.1002/per.429
|View full text |Cite
|
Sign up to set email alerts
|

Thinking styles and the five‐factor model of personality

Abstract: The primary aim of this study was to investigate the relationships between thinking styles and the big five personality dimensions. Four hundred and eight (149 males, 259 females) university students from Shanghai, mainland China, responded to the Thinking Styles Inventory and the NEO Five‐Factor Inventory. It was found that thinking styles and personality dimensions overlap to a degree. As predicted, the more creativity‐generating and more complex thinking styles were related to the extraversion and openness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 34 publications
6
41
1
Order By: Relevance
“…Similar to Zhao and Seibert [62], Rauch and Frese [63] found that entrepreneurs had higher levels of Extraversion, while rated comparatively lower on Agreeableness [21,63]. In addition, Zhang and Huang [64] combined cognition and personality traits, and found that Openness was positively associated with innovation. [23,24,65].…”
Section: Big Six Personality Related To Entrepreneurial Intentionmentioning
confidence: 68%
“…Similar to Zhao and Seibert [62], Rauch and Frese [63] found that entrepreneurs had higher levels of Extraversion, while rated comparatively lower on Agreeableness [21,63]. In addition, Zhang and Huang [64] combined cognition and personality traits, and found that Openness was positively associated with innovation. [23,24,65].…”
Section: Big Six Personality Related To Entrepreneurial Intentionmentioning
confidence: 68%
“…Thinking styles that are more creative and that require higher levels of cognitive complexity (e.g., legislative, judicial, global, hierarchical, and liberal styles-labeled as "Type I thinking styles") were related to higher levels of self-esteem (Zhang, 2001a;Zhang and Postiglione, 2001), higher cognitive-developmental levels (Zhang, 2002a), the personality trait of openness to experience (Zhang, 2002b,c;Zhang and Huang, 2001), and a stronger sense of purposefulness concerning vocational purpose, avocational-recreational purpose, and style of life (Zhang, 2002d). Moreover, thinking styles that suggest favoring of norms and that denote lower levels of cognitive complexity (e.g., the executive, local, monarchic, and conservative styles-labeled as "Type II thinking styles") were related to lower self-esteem, lower cognitive-developmental levels, the personality trait of neuroticism, and a lack of sense of purposefulness.…”
Section: Value-laden Versus Value-freementioning
confidence: 98%
“…This prediction was based on the following reasoning: As a relatively new component in education, CIT, like any other new events, may be better received by students who are more open-minded. Previous research revealed that Type I thinking styles are positively related to open-mindedness (Zhang & Huang, 2001). Therefore, it was predicted that Type I thinking styles would significantly contribute to better knowledge and more frequent use of CIT and to a more favorable attitude towards the use of CIT in education.…”
Section: Theory Of Mental Self-governmentmentioning
confidence: 98%